The Sequential Dynamics of Indonesia's Decentralization Reform: Explaining Intergovernmental Power Redistribution through Faletti's Sequential Theory - Anindita Irvan Wiryawan; Rosyid Ridlo Al-Hakim; Endro Sariono; Rifki Arif; Ady Setyo Nugroho (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Indonesia has implemented one of the world's most ambitious decentralization reforms since the 1998 Reformasi, transferring extensive administrative responsibilities, fiscal resources, and political authority to regional governments. Despite these institutional changes, the redistribution of intergovernmental power remains contested. Existing studies primarily examine administrative, fiscal, and political decentralization as separate institutional dimensions, offering limited explanation of how their sequencing shapes long-term central–local power relations. This study analyzes Indonesia's decentralization reform through Faletti's Sequential Theory of Decentralization using a normative legal research design supported by historical institutional analysis. Primary legal materials, including constitutional provisions and decentralization legislation enacted between 1999 and 2022, were examined alongside relevant scholarly literature. The findings indicate that Indonesia's decentralization followed an Administrative–Fiscal–Political (A→F→P) sequence in which administrative responsibilities were transferred before fiscal strengthening and political consolidation at the regional level. This sequence expanded regional governmental functions while preserving the central government's strategic control over institutional development and policy coordination. The study demonstrates that reform sequencing provides a more comprehensive explanation of Indonesia's decentralization trajectory than analyses focusing solely on legal or fiscal reforms. It also extends the application of Faletti's framework to a unitary state outside Latin America, contributing a process-oriented perspective for understanding intergovernmental power redistribution in decentralized governance.